Taman Arkeologi Leang-Leang di Era Digital: Studi Interdisipliner Antara Wisata Edukatif dan Ruang Produksi Konten - Liza Dwi Eftiza Khairunniza; Angga Yuda Sakti (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humani..., 2026)
Exploring the shifting function of the Leang-Leang Archaeological Park in Maros in the digital era has become an interesting phenomenon. Leang-Leang Archaeological Park is a prehistoric heritage site that holds significant educational and historical value in Indonesia. However, the development of social media in the digital era has influenced the way visitors utilize this cultural space, particularly as a location for visual content production. This study aims to analyze the transformation of the Leang-Leang Archaeological Park from an educational space into a digital content production space and to understand the influence of social media on visitor behavior. This research employed a descriptive qualitative approach through field observations, visual documentation, and semi-structured interviews with visitors and park managers. The findings indicate that most visitors are more interested in the visual and aesthetic aspects of the site than in its educational value. Museum areas and information panels tend to receive less attention, while visually attractive spots are more frequently used for photography and social media content creation. This phenomenon reflects a shift in the meaning of cultural spaces due to the growth of digital culture and the need for self-representation on social media. This study emphasizes the importance of management strategies that integrate educational approaches with digital technology in order to preserve the historical function and cultural value of the Leang-Leang Archaeological Park in the digital era.